2008
DOI: 10.1111/j.1600-6143.2008.02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Deceased Organ Donor Characteristics and Clinical Interventions Associated with Organ Yield

Abstract: While the function of each organ is used by each transplant team to assess suitability for transplantation, little is known about the donor characteristics and clinical interventions that contribute toward overall organ transplantation potential. We conduct a retrospective review of United Network for Organ Sharing (UNOS) deceased donor registry data from January 2005 to December 2006. This registry contains all deceased donors from whom organs were recovered during this time period (n = 15 601). Ordinary leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 14 publications
0
34
0
6
Order By: Relevance
“…Typically 1-2 μg IV are required every 6 hours (137). Retrospective studies have suggested that desmopressin administration in the potential adult or pediatric organ donor with DI is associated with hemodynamic stability and perhaps increased yield of donor organs (150,151).…”
Section: How Should Avp Deficiency In the Organ Donor Be Treated?mentioning
confidence: 99%
“…Typically 1-2 μg IV are required every 6 hours (137). Retrospective studies have suggested that desmopressin administration in the potential adult or pediatric organ donor with DI is associated with hemodynamic stability and perhaps increased yield of donor organs (150,151).…”
Section: How Should Avp Deficiency In the Organ Donor Be Treated?mentioning
confidence: 99%
“…Aggressive donor management (ADM) improves both quality and quantity of organs available for transplant [198]. Current ADM recommendations include early identification of potential donors, ICU admission, pulmonary artery catheterisation, aggressive fluid management, vasopressors, hormonal resuscitation therapy, pulmonary toilet, and bronchoscopy [148, 199202].…”
Section: Management Implications and Potential Future Directionsmentioning
confidence: 99%
“…7 Standard pretreatment regimens to counteract the effects of brain death on organ function and transplant outcome usually include the administration of methyl prednisolone and vasopressin. 7 Brain death is character ized by severe cardiovascular dysregulation. Ischaemia and malperfusion in the cardiovascular nuclei of the medulla oblongata lead to massive catecholamine release and hypertension.…”
Section: Pretreatment Measuresmentioning
confidence: 99%